2013
DOI: 10.1177/0037549713496153
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation methodology of the Nuss procedure surgical planner

Abstract: Surgical planners are used to achieve the optimal outcome for surgery. They are especially desired in procedures where a positive aesthetic outcome is the primary goal, such as the Nuss procedure which is a minimally invasive surgery for correcting pectus excavatum (PE) -a congenital chest wall deformity which is characterized by a deep depression of the sternum. The Nuss procedure consists of placement of a metal bar(s) underneath the sternum, thereby forcibly changing the geometry of the ribcage. Because of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…A similar approach has been adopted by Tonutti et al [29] for predicting the movement of a tumor during brain surgery, but the displacement of the healthy tissue is not considered. Rechowicz et al [23] estimate the displacement of a patient's rib cage, but only predict the displacement of surface nodes. In contrast, Marooka et al [18] estimate the displacement of a full liver model using neural networks by superimposing basic deformation modes.…”
Section: Related Workmentioning
confidence: 99%
“…A similar approach has been adopted by Tonutti et al [29] for predicting the movement of a tumor during brain surgery, but the displacement of the healthy tissue is not considered. Rechowicz et al [23] estimate the displacement of a patient's rib cage, but only predict the displacement of surface nodes. In contrast, Marooka et al [18] estimate the displacement of a full liver model using neural networks by superimposing basic deformation modes.…”
Section: Related Workmentioning
confidence: 99%
“…Regarding the material properties of both ribs (cortical/trabecular) and sternum, there has been a consensus in the field that bone structures are considered isotropic, homogeneous and linear elastic materials 16,25 . On the other hand, there is no agreement concerning the material properties of PE cartilages 21 , where studies suggested that age and calcification can influence the biomechanical properties 26,27 , which have the potential to affect its structural behavior 28 . In this sense, material properties for the bone and cartilage were considered isotropic, homogeneous and linearly elastic.…”
Section: Generation Of the Patient-specific Biomechanical Modelmentioning
confidence: 99%
“…Along the years, several studies explored the Nuss procedure using FEM to analyze the chest wall evolution where three-dimensional (3D) models were generated from the reconstruction of CT data. Briefly, these studies focused on the: i) comparison of stress distribution between adult and child patients 15 ; ii) analysis of the forces on the thoracic cage of asymmetric PE patients 16 ; iii) dynamic effects on the spine of patients with asymmetric chest 17 ; iv) correction bar positioning simulation 18,19 ; v) effect of additional bar application on the patient's postoperative pain 20 ; vi) generation of parametric models to create a simplification of a 3D chest model using CT measurements and chest surface scans 21 ; vii) simultaneous correction of PE and scoliosis 22 ; and, viii) methodologies to individually design and optimize the shape of the Nuss bar, advising the location of the incisions using CT data of the patient 23 . Although the relevant advances of these studies, we considered that different drawbacks are presented in each one, namely: the limited sample size (most studies are limited to 1-2 cases); the neglection of the inherent variability, properties, and specificity of each anatomical structure during simulation; the disregard of the skin as a crucial structure to verify the aesthetical outcome; the neglection of the real shape of the bar; and, the fact that the real surgical outcome was frequently not considered as the ground truth.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, clinical studies focusing on asymmetric PEX are underway. However, biomechanical studies have mainly concentrated on simulations of symmetric PEX (Chang et al, 2008;Ho Quoc et al, 2013;Rechowicz and McKenzie, 2013;Ghionzoli et al, 2014;Rechowicz et al, 2014;Ye et al, 2017;Sesia et al, 2019;Wang et al, 2022). Further biomechanical studies on severe types are needed, such as the FE method study by Nagasao et al, which showed that the Nuss procedure for asymmetric PEX has a dynamic effect on the spine (Nagasao et al, 2010).…”
Section: Introductionmentioning
confidence: 99%